1983
DOI: 10.1042/bj2090741
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a rabbit bone metalloproteinase that degrades proteoglycan and other connective-tissue components

Abstract: A metalloproteinase, 'proteoglycanase', that degrades proteoglycan and insoluble type IV collagen as well as casein was purified to homogeneity from rabbit bone culture medium. The major form of this proteinase had a final specific activity of 2400 micrograms of casein degraded/min per mg of enzyme protein, and Mr 24 500 by sodium dodecyl sulphate/polyacrylamide-gel electrophoresis or 12 500 by gel-filtration chromatography. It was active over the pH range 5.0-9.0 against a number of substrates, and the rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
110
1
2

Year Published

1984
1984
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(119 citation statements)
references
References 28 publications
6
110
1
2
Order By: Relevance
“…However, the molecular size of these enzymes on gel filtration is highly variable. In at least one case this has been attributed to the degree of purification of the enzyme [40]. Although 0.05% v/v Tween 20 was present in buffers used with the ROS 17/2 enzymes, the collagenase and gelatinase activities were not separated.…”
Section: Discussionmentioning
confidence: 99%
“…However, the molecular size of these enzymes on gel filtration is highly variable. In at least one case this has been attributed to the degree of purification of the enzyme [40]. Although 0.05% v/v Tween 20 was present in buffers used with the ROS 17/2 enzymes, the collagenase and gelatinase activities were not separated.…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatoid synovial fibroblasts in culture secrete three distinct matrix metalloproteinases (MMPs): MMP-1 corresponds to collagenase (EC 3.4.24.7) [1], MMP-2 to 'gelatinase' and type IV collagenase [2][3][4][5] and MMP-3 to stromelysin [6][7][8]. Collagenase digests type I, II, III and X [9] collagens.…”
Section: Introductionmentioning
confidence: 99%
“…MMP-2 is thought to be involved in the degradation of collagen by digesting gelatin derived from collagen molecules cleaved by the action of collagenase [2], although the ability of the enzyme to digest type IV and type V collagens has been pointed out [4,5]. MMP-3 has a broad range of activities to extracellular macromolecules; it degrades proteoglycans, type IV collagen, laminin, fibronectin and gelatin, and removes N-terminal propeptides of type I procollagen [6][7][8]. We have recently demonstrated that MMP-3 also digests type IX collagen which has an important role in Correspondence address: Y. Okada, Department of Pathology, School of Medicine, Kanazawa University, 13-1 Takara-machi, Kanazawa 920, Japan maintaining the structural integrity of cartilage [10].…”
Section: Introductionmentioning
confidence: 99%
“…Human leucocyte collagenase and gelatinase were prepared as published [16]. Purified rabbit bone gelatinase was a gift from C. Poll, Strangeways Laboratory (unpublished) and purified protcoglycanase was prepared by our published method [17]. Rabbit kidney metalloendopeptidase was a gift from Dr. M. Orlowski, prepared as published [18].…”
Section: Properties Of Purtiully Purified Collugenase Inhibitorsmentioning
confidence: 99%